Lignocellulosic composites from brazilian giant bamboo (Guadua magna). Part 2: Properties of cement and gypsum bonded particleboards - C. de Araújo, Priscila; M. Arruda, Larissa; H. S. Del Menezzi, Cláudio; E. Teixeira, Divino; de Souza, Mário R. (Maderas. Ciencia y Tecnología, 2014)
In the first part of this study, the feasibility of manufacturing resin-bonded particleboard from the recently identified Brazilian giant bamboo (Guadua magna) was evaluated. In this second part, the main goal was to study the material properties of the cement and gypsum-composites made from that bamboo species. The effect of CaCl2 addition in the physical and mechanical properties was also evaluated. Initially, the hydration test was performed to determine the inhibition index of the bamboo particles in the cement and gypsum setting. Three concentrations of CaCl2 were used to produce bamboo cementbonded particleboards (BCBP): 0%, 2% and 4%. CaCl2 was not added into bamboo gypsum-bonded particle boards (BGBP). Mechanical and physical properties were evaluated and nondestructive testing was performed as well. The inhibition index of Guadua magna in the cement or gypsum setting was classified as “low inhibition”. The addition of CaCl2 at bamboo-cement boards increased the internal >bonding and reduced the water absorption. Other properties were not significantly affected. The bamboocement boards presented higher bending strength and lower moisture content than bamboo-gypsum boards.